2021
DOI: 10.33073/pjm-2021-034
|View full text |Cite
|
Sign up to set email alerts
|

Latent Pathogenic Fungi in the Medicinal Plant Houttuynia cordata Thunb. Are Modulated by Secondary Metabolites and Colonizing Microbiota Originating from Soil

Abstract: Latent pathogenic fungi (LPFs) affect plant growth, but some of them may stably colonize plants. LPFs were isolated from healthy Houttuynia cordata rhizomes to reveal this mechanism and identified as Ilyonectria liriodendri, an unidentified fungal sp., and Penicillium citrinum. Sterile H. cordata seedlings were cultivated in sterile or non-sterile soils and inoculated with the LPFs, followed by the plants’ analysis. The in vitro antifungal activity of H. cordata rhizome crude extracts on LPF were determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It is only reported that pathogenic fungi influence H. cordata growth and its metabolite accumulation. 10 However, no study has investigated the link between promoting H. cordata growth and PGPE, in addition to the regulatory mechanisms associated with the metabolic signals. Biotic and abiotic stresses interfere with metabolic signals of plants (e.g., cytokinin, abscisic acid, and jasmonic acid signaling), which modulate plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is only reported that pathogenic fungi influence H. cordata growth and its metabolite accumulation. 10 However, no study has investigated the link between promoting H. cordata growth and PGPE, in addition to the regulatory mechanisms associated with the metabolic signals. Biotic and abiotic stresses interfere with metabolic signals of plants (e.g., cytokinin, abscisic acid, and jasmonic acid signaling), which modulate plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…19 Colonizing microbial communities in soils with H. cordata can inhibit pathogenic fungi and promote accumulation of secondary metabolites. 10 However, whether PGPE promotes the accumulation of secondary metabolites in H. cordata and the regulatory mechanisms of the metabolic signals remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation